Evaluation of the clinical and economic impact of delays to surgery in patients with periampullary cancer. Issue 4 (2nd April 2019) - Pandé, R; Hodson, J; Murray, A; Marcon, F; Kalisvaart, M; Marudanayagam, R; Sutcliffe, R P; Mirza, D F; Isaac, J; Roberts, K J
Abstract: Background: Early treatment is the only potential cure for periampullary cancer. The pathway to surgery is complex and involves multiple procedures across local and specialist hospitals. The aim of this study was to analyse variability within this pathway, and its impact on cost and outcomes. Methods: Patients undergoing surgery for periampullary cancer (2011–2016) were identified retrospectively and their pathway to surgery was analysed. Patients who had early surgery (shortest quartile, Q1) were compared with those having late surgery (longest quartile, Q4). Results: A total of 483 patients were included in the study, with 121 and 124 patients in Q1 and Q4 respectively. The median time from initial CT to surgery was 21 days for Q1 versus 112 days for Q4 ( P < 0·001). Diagnostic delays were common in Q4; these patients required significantly more investigations than those in Q1 (endoscopic ultrasonography (EUS): 74·2 versus 18·2 per cent respectively, P < 0·001; MRI: 33·6 versus 20·6 per cent, P = 0·036). The median time to diagnostic EUS was 13 days in Q1 versus 59 days in Q4 ( P < 0·001). Some 42·1 per cent of jaundiced patients in Q1 underwent preoperative biliary drainage, compared with all patients in Q4. There were significantly more unplanned admissions and associated longer duration of hospital stay per patient and costs in Q4 than in Q1 (median: 8 versus 3 days respectively; €5652 versus €2088; both P < 0·001). There was a higher likelihood of potentially curative surgery in Q1 (82·6 per cent versus 66·9 per cent in Q4; P = 0·005). Conclusion: There is wide variation across the entire pathway, suggesting that multiple strategies are required to enable early surgery. Defining an effective pathway by anticipating the need for investigations and avoiding biliary drainage reduces unplanned admissions and costs and increases resection rates. Graphical Abstract: Periampullary cancer necessitates early treatment to improve outcome, but has a complex pathway to surgery. Wide variation across the entire pathway suggests that multiple strategies are required to enable early operation. Defining an effective pathway by anticipating the need for investigations and avoiding preoperative biliary drainage may reduce unplanned admissions and costs. Shorter delays increase resection rates, lowers costs